Penerapan Trilogi Kepemimpinan Ki Hajar Dewantara Terhadap Kinerja Guru SMA - Eni Zakhanah (Media Manajemen Pendidikan, 2022)
The purpose of this research in general is to find out the contribution of Ki Hajar Dewantara's leadership trilogy to the performance of teachers in SMA in Kapanewon Imogiri. Meanwhile, specifically, this study aims to analyze the contribution of Ki Hajar Dewantara's leadership trilogy on the aspect of ing ngarsa sung tuladha on teacher performance in high school in Kapanewon Imogiri. The contribution of Ki Hajar Dewantara's leadership trilogy in the aspect of ing madya mangun karsa. The contribution of Ki Hajar Dewantara's leadership trilogy on the Tut wuri handayani aspect. This research uses quantitative research. The population in this study were all teachers in SMA in Kapanewon Imogiri. Data collection techniques with questionnaires. The data analysis technique used multiple regression analysis. After the validity and reliability tests were carried out, it was found that of all statements of variable “performance” declared valid and reliable, all statements of the Ki Hajar Dewantara’s leadership trilogy in the aspect of ing ngarsa sung tuladha variable declared valid and reliable, all statements on the Ki Hajar Dewantara’s leadership trilogy in the aspect of ing madya mangun karsa variable all declared valid and reliable, as well as all statements on the variable Ki Hajar Dewantara’s leadership trilogy in the aspect of tut wuri handayani is declared valid and reliable. The results of this study indicate that: There is a positive and significant influence together with the leadership trilogy of Ki Hadjar Dewantara on the performance of teachers in Imogiri. This means that the higher the understanding and application of Ki Hadjar Dewantara's leadership trilogy, the better the teacher's performance will be. On the other hand, if the understanding and application of Ki Hajar Dewantara's leadership trilogy is low, then the performance produced by the teacher is also low. There is a positive and significant influence between the leadership trilogy of Ki Hadjar Dewantara on the aspect of ing ngarsa sung tuladha on teacher performance. There is a positive and very significant influence between Ki Hadjar Dewantara's leadership trilogy on the ing madya mangun karsa aspect on teacher performance. There is a positive and significant influence between Ki Hajar Dewantara's leadership trilogy on the tut wuri handayani aspect on teacher performance. Of the three independent variables, the dominant influence on teacher performance is the ing madya mangun karsa aspect. Keywords: performance, konstribution, leadership trilogy